Demand-side response power control strategy considering load production sequence requirements - Wang, Xi; Chen, Zhen; Xie, Haocong; Liao, Siyang; Ye, Xi; Chen, Gang (Frontiers in Energy Research, 2024)
With the introduction of a high proportion of new energy sources, the power system needs new means to enhance its regulating flexibility. High-energy-consuming industrial loads on the demand side have significant potential to improve the grid’s regulating flexibility. Unplanned power adjustments can affect normal load production. This paper proposes a power control strategy that considers the normal production order of loads, aiming to balance load response capacity requirements and safe production order. Taking copper electrolysis load as an example, based on the load process flow and the power characteristics of production equipment, factors affecting load production order and methods for calculating impact weights are analyzed, and a strategy to reduce the demand response to production order caused by power control is proposed. The effectiveness of the power control strategy is verified through simulation examples, providing a feasible solution for industrial loads to participate in demand-side response.